Legalitas Retribusi dan Praktik Pungli terhadap UMKM Street Food di Sekitar Kampus Universitas Negeri Gorontalo - Sholeh, Muhammad; W. Badu, Lisnawaty; Towadi, Mellisa (Cv. Kalimasada Group, 2025)
The practice of illegal levies against street food UMKM actors in the campus area of ​​Gorontalo State University has become a serious problem because it is carried out without a clear legal basis and is coercive. In fact, the area is not included in the official retribution zone according to the Gorontalo City Regulation, so a legal study and active role of the police are needed to overcome extortion that is detrimental to small business actors. This study aims to examine the regulation of levies and the practice of extortion against Micro, Small, and Medium Enterprises (MSMEs) in the street food model in the Gorontalo State University campus area and to analyze the role of the police in handling these problems. This study uses an empirical method with a normative legal approach. The results of the study show that the Gorontalo State University campus area is not included in the official locations subject to levies based on Gorontalo City Regional Regulation Number 6 of 2020 concerning Business Service Levies, because it is not classified as a place for recreation and sports. However, in practice, MSME actors in the area are subject to levies by parties who do not have legal authority, under the pretext of security and cleanliness. These levies are coercive and are not based on a valid legal basis, thus fulfilling the elements of the crime of extortion as regulated in Article 368 of the Criminal Code. In terms of law enforcement, the Kota Tengah Police as the police in charge in the area have not been able to act actively because there have been no official reports from the public. This shows the weak courage of MSME actors in reporting, which is the main obstacle in eradicating extortion. Therefore, proactive steps are needed from the local government to re-regulate the legal zone of retribution, as well as active involvement of the police in taking a preventive approach to the community in order to prevent and overcome the practice of extortion that is detrimental to small business actors.